2020
DOI: 10.1101/2020.06.24.20133249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-world Experience with Favipiravir for Treatment of COVID-19 in Thailand: Results from a Multicenter Observational Study

Abstract: Background. Favipiravir is a broad−spectrum oral antiviral agent that shows in vitro activity against SARS−CoV−2. Presently, data on the effectiveness and optimal dosage of favipiravir for treating COVID−19 is limited. Methods. We conducted a retrospective observational study of hospitalized adult patients with COVID-19 at five tertiary care hospitals in Thailand. We reviewed patient charts to obtain all necessary data. Results. Among 247 COVID-19 patients, 63 (23.0%) received ≥1 dose of favipiravir. O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 12 publications
1
44
1
2
Order By: Relevance
“…Selective reporting may have been a problem in Chen's study because of the limited observation time frame. It is important to determine the appropriate dose and duration of treatment with FVP because low dose therapy is found to be a bad prognostic factor for clinical improvement and widespread variations in treatment duration among studies and lack of effective plasma concentrations of drug in critically ill patients [11,12]. Because of the early evidence of potential bene ts shown by this drug in clinical improvement as well as imaging improvement, it is necessary to conduct large scale prospective, double-blind randomized controlled trials to further increase the power of the study and eliminate biases so that de nitive advice for treatment can be given in the coming days.…”
Section: Discussionmentioning
confidence: 99%
“…Selective reporting may have been a problem in Chen's study because of the limited observation time frame. It is important to determine the appropriate dose and duration of treatment with FVP because low dose therapy is found to be a bad prognostic factor for clinical improvement and widespread variations in treatment duration among studies and lack of effective plasma concentrations of drug in critically ill patients [11,12]. Because of the early evidence of potential bene ts shown by this drug in clinical improvement as well as imaging improvement, it is necessary to conduct large scale prospective, double-blind randomized controlled trials to further increase the power of the study and eliminate biases so that de nitive advice for treatment can be given in the coming days.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 viral RNA-dependent RNA polymerase, crucial for coronavirus replication and transcription, is a promising drug target for the treatment of COVID-19 [1]. Nucleoside analogues, including remdesivir, sofosubivir and favipiravir (T-705), have been shown to have a broad spectrum of activity against viral polymerases [2], and are being trialed against SARS-CoV-2 infections [3,4,5]. Recent results of the World Health Organization SOLIDARITY clinical trials indicate that remdesivir, hydroxychloroquine, lopinavir and interferon treatment regimens appeared to have little or no effect on hospitalized COVID-19 patients, as measured by overall mortality, initiation of ventilation and duration of hospital stays [6], so insight into the modes action and mechanisms of current and future drugs for COVID-19 is increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Favipiravir is an oral purine nucleic acid analog similar to remdesivir with broad in vitro activity against many RNA viruses and is currently licensed in Japan for use in the treatment of influenza virus 288–290 . There are comparatively few clinical studies to date that have evaluated favipiravir against COVID‐19, but those studies that have been done show reduction in the SARS‐CoV‐2 viral load and argue for additional studies 291–293 . One open‐label control study compared favipiravir versus lopinavir for the treatment of COVID‐19 291 .…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
“…The clinical recovery rate at 7 days was 71.43% for the favipiravir group versus 55.86% for the arbidol group ( p = .0199) 292 . A retrospective observational study of hospitalized adult patients with COVID‐19 ( n = 247) at five tertiary care hospitals in Thailand found that the 63 patients receiving favipiravir had a day‐7 clinical improvement of 71.4% while patients not receiving had a day‐7 clinical improvement of 67.7% 293 . The rate of clinical improvement of the favipiravir group by day‐28 was 83.3%.…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%